COLREG Convention on the International Regulations for Preventing Collisions at Sea, 1972 - OMI (Londres, Inglaterra Organización Marítima Internacional, 2003)
Esta publicación contiene el texto totalmente consolidado de la Convención de 1972. Sustituye a la edición consolidada de 2002, que contiene el texto que estaba en vigor antes del 29 de noviembre de 2003 más las enmiendas de 2001 por separado. -- Descripción del editor
Convention on the International Regulations for Preventing Collisions at Sea, 1972, as amended International Regulations for Preventing Collisions at Sea, 1972, as amended: General ; Steering and sailing rules ; Lights and shapes ; Sound and light signals ; Exemptions ; Annex 1. Positioning and technical details of lights and shapes ; Annex 2. Additional signals for fishing vessels fishing in close proximity ; Annex 3. Technical details of sound signal appliances ; Annex 4. Distress signals
Keywords: COLISIONES MARITIMAS -- ABORDAJE - PREVENCION -- DERECHO MARITIMO INTERNACIONAL